On uniform detection in space - Gečiauskas, E. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. Гечяускас. О равномерном поиске в пространстве E. Gečiauskas. Apie tolygią paiešką erdvėje